The human resource professionals' career guide : building a position of strength - Palmer, Jeanne, 1948- (Pfeiffer, 2004)
"Written by Jeanne Palmer, The Human Resource Professional's Career Guide is the first comprehensive look at the choices, challenges, and rewards of buildings a life's work in HR. Whether you are new to the field or you are wondering how to best leverage the value of all your experiences to make the next big career leap, this book gives you all the information you need to know to make smart career decisions."--BOOK JACKET.